Effect of Fenton pre-oxidation on mobilization of nutrients and efficient subsequent bioremediation of crude oil-contaminated soil. (August 2017) - Xu, Jinlan; Kong, Fanxing; Song, Shaohua; Cao, Qianqian; Huang, Tinglin; Cui, Yiwei
Abstract: Fenton pre-oxidation and a subsequent bioremediation phase of 80 days were used to investigate the importance of matching concentration of residual indigenous bacteria and nutrient levels on subsequent bioremediation of crude oil. Experiments were performed using either high (>10 7.7 ± 0.2 CFU/g soil) or low (<10 5.9 ± 0.1 CFU/g soil) concentrations of bacteria and three different nutrient levels: enough (C/N > 9.8), moderate (C/N:5–9.8), and lacking nutrient level (C/N < 5) conditions. Weak Fenton pre-oxidation (225 mM H2 O2 and 2.9 mM Fe 2+ ) resulted in highly matching between nutrient level and the population of residual indigenous bacteria. Up to 53% of total petroleum hydrocarbon (TPH) and 58% of main hydrocarbon (C15 C25, during the first 10 days) were removed from the soil. Under matching conditions, the activity of indigenous bacteria and nutrient mobilization were enhanced, promoting the bioremediation of crude oil. In addition, the biodegradation of long chain molecules (C26 C30 ) required a high level of NH4 + -N. Highlights: Weak Fenton pre-oxidation resulted in highly matching between nutrient and population of residual indigenous bacteria. The activity of indigenous bacteria was enhanced under highly matching condition. The nutrients were mobilized faster at highly matching condition. Highly matching between nutrient and population of residual indigenous bacteria improved bioremediation of TPH.